Search for a low-mass standard model Higgs boson in the ττ decay channel in pp collisions at sqrt[s]=1.96 TeV. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2012)
We report on a search for the standard model Higgs boson decaying into pairs of τ leptons in pp collisions produced by the Tevatron at sqrt[s]=1.96  TeV. The analyzed data sample was recorded by the CDFII detector and corresponds to an integrated luminosity of 6.0  fb(-1). The search is performed in the final state with one τ decaying leptonically and the second one identified through its semihadronic decay. Since no significant excess is observed, a 95% credibility level upper limit on the production cross section times branching ratio to the ττ final state is set for hypothetical Higgs boson masses between 100 and 150  GeV/c2. For a Higgs boson of 120  GeV/c2 the observed (expected) limit is 14.6 (15.3) the predicted value.